Midbrain Dopamine Neurons Defined by TrpV1 Modulate Psychomotor Behavior - Serra, Gian Pietro; Guillaumin, Adriane; Dumas, Sylvie; Vlcek, Bianca; Wallén-Mackenzie, Åsa (Frontiers in Neural Circuits, 2021)
Dopamine (DA) neurons of the ventral tegmental area (VTA) continue to gain attention as far more heterogeneous than previously realized. Within the medial aspect of the VTA, the unexpected presence of TrpV1 mRNA has been identified. TrpV1 encodes the Transient Receptor Potential cation channel subfamily V member 1, TRPV1, also known as the capsaicin receptor, well recognized for its role in heat and pain processing by peripheral neurons. In contrast, the brain distribution of TrpV1 has been debated. Here, we hypothesized that the TrpV1+ identity defines a distinct subpopulation of VTA DA neurons. To explore these brain TrpV1+ neurons, histological analyses and Cre-driven mouse genetics were employed. TrpV1 mRNA was most strongly detected at the perinatal stage forming a band of scattered neurons throughout the medial VTA, reaching into the posterior hypothalamus. Within the VTA, the majority of TrpV1 co-localized with both Tyrosine hydroxylase (Th) and Vesicular monoamine transporter 2 (Vmat2), confirming a DA phenotype. However, TrpV1 also co-localized substantially with Vesicular glutamate transporter 2 (Vglut2), representing the capacity for glutamate (GLU) release. These TrpV1+/Th+/Vglut2+/Vmat2+ neurons thus constitute a molecularly and anatomically distinct subpopulation of DA-GLU co-releasing neurons. To assess behavioral impact, a TrpV1Cre-driven strategy targeting the Vmat2 gene in mice was implemented. This manipulation was sufficient to alter psychomotor behavior induced by amphetamine. The acute effect of the drug was accentuated above control levels, suggesting super-sensitivity in the drug-na ve state resembling a “pre-sensitized” phenotype. However, no progressive increase with repeated injections was observed. This study identifies a distinct TrpV1+ VTA subpopulation as a critical modulatory component in responsiveness to amphetamine. Moreover, expression of the gene encoding TRPV1 in selected VTA neurons opens up for new possibilities in pharmacological intervention of this heterogeneous, but clinically important, brain area.